Factors Associated with Receiving No Maternal or Neonatal Interventions among Periviable Deliveries - Perry, Madeline F.; Hajdu, Sierra; Rossi, Robert M.; DeFranco, Emily A. (American Journal of Perinatology, 2022)
Objective The aim of this study was to quantify the influence of maternal sociodemographic, medical, and pregnancy characteristics on not receiving maternal and neonatal interventions with deliveries occurring at 22 to 23 weeks of gestation.Study design This was a case–control study of U.S. live births at 220/6 to 236/7 weeks of gestation using vital statistics birth records from 2012 to 2016. We analyzed births that received no interventions for periviable delivery. Births were defined as having no interventions if they did not receive maternal (cesarean delivery, maternal hospital transfer, or antenatal corticosteroid administration) or neonatal interventions (neonatal intensive care unit admission, surfactant administration, antibiotic administration, or assisted ventilation). Logistic regression estimated the influence of maternal and pregnancy factors on the receipt of no interventions when delivery occurred at 22 to 23 weeks.Results Of 19,844,580 U.S. live births in 2012–2016, 24,379 (0.12%) occurred at 22 to 23 weeks; 54.3% of 22-week deliveries and 15.7% of 23-week deliveries received no interventions. Non-Hispanic Black maternal race was associated with no maternal interventions at 22 and 23 weeks. Private insurance, singleton pregnancy, and small for gestational age were associated with receiving no neonatal interventions at 22 and 23 weeks of gestation.Conclusion Withholding or refusing maternal and neonatal interventions occurs frequently at the threshold of viability. Our data highlight various sociodemographic, pregnancy, and medical factors associated with decisions to not offer or receive maternal or neonatal interventions when birth occurs at the threshold of viability. The data elucidate observed practices and may assist in the development of further research.Key Points
Keywords: periviable birth; race and ethnicity; socioeconomic status; preterm birth; interventions